Experimental Investigation of Using E10 and E15 Blend Fuels as a Fuel on Performance Parameters of the Cooling System of an Engine - Adugnaw Nurlgn; Ramesh Babu Nallamothu (Journal of Engineering)
This research investigates the impact of E10 and E15 fuel blends on the cooling system performance parameter of an engine compared to pure gasoline. The paper was done by experimenting on a CT 400.01 four-cylinder, four-stroke, water-cooled petrol engine. Various parameters were recorded during the experiments, including the cooling water outlet temperature, lubrication oil temperature, exhaust gas temperature, cooling water flow rate, and the speed of the radiator cooling fan. Measurements were taken under both no load conditions and at 15% engine load, with speeds ranging from 1110 to 4535 rpm. The findings indicate that using the E10 blend fuel elevates the cooling water outlet temperature by up to 6.85% at no load and 4.54% at 15% engine load. The lubrication oil temperature rises by as much as 6.15% at no load and 5% at 15% load, while the exhaust gas temperature increases by 5.34% at no load and 6.93% at 15% load. In the case of E15 blend fuel, the cooling water outlet temperature increases by up to 8.33% at no load and 6.38% at 15% load. The lubrication oil temperature increases by up to 9.72% at no load and 7.42% at 15% load, and the exhaust gas temperature rises by 9.64% at no load and 8.51% at 15% load. Additionally, using E10 and E15 blends significantly affects the cooling water flow rate compared to pure gasoline. At no load, the E10 blend can reduce the cooling water flow rate by up to 50%, while the E15 blend reduces it by up to 31.8%. Under a 15% engine load, E10 blend fuels decrease the cooling water flow rate by up to 45.5%, and E15 blends reduce it by up to 35.57%. The experiment also shows that employing E10 and E15 blends has a minimal effect on the rotational speed of the radiator cooling fan. At no load, the fan speed for pure gasoline is greater than that of the E15 blend by a maximum of 0.28% and the E10 blend by up to 0.12%, with deviations of no more than 0.04%. Under 15% load, the fan speed of the E10 blend is higher than that of pure gasoline by a maximum of 0.22%, with a difference of less than 0.05%. Meanwhile, the fan speed of the E15 blend exceeds that of pure gasoline by a maximum of 0.22% and less than 0.06%.